Herpes Zoster and Postherpetic Neuralgia: Past, Present and Future - Gary J Bennett; C Peter N Watson (Pain Research and Management)
OBJECTIVES: The history behind the current understanding of the varicella-zoster virus and its relationship to the pain conditions caused by shingles and postherpetic neuralgia are reviewed. The framework for the current conceptualization is Hope-Simpson’s latency hypothesis. Data from recent work in virology, neuroanatomy and epidemiology are reviewed, as is work using varicella-zoster virus-infected animals. The recent data largely confirm Hope-Simpson’s hypothesis and extend it significantly.